A quick-drying water-based emulsion and a preparation method thereof
Patent Information
- Application Number
- CN202310556033.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-17
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-05-17
AI Technical Summary
在溶剂型油墨中聚合物分子以分子链舒展的状态存在于溶剂中,在成膜过程中随着溶剂的挥发,分子链充分扩散、相互缠绕,最后形成均匀的致密膜;而乳液印刷油墨的成膜过程则较为复杂
[0030]与现有技术相比,本发明的有益效果在于:本发明提供的水性乳液,具有特殊的“硬壳-梯度核”的结构,可以在保证成膜强度的前提下,大幅提升传统水性乳液树脂的初干性(涂膜表面干燥)及实干性(涂膜里层干燥),该乳液还具有粒径细、抗剪切性能好,储存稳定性佳,附着牢度强等优点。有望作为主体成膜树脂应用于非渗透性基材的水性油墨,从而提升水墨的干燥速度。
Smart Images

Figure QLYQS_1 
Figure BDA0004233039190000031 
Figure BDA0004233039190000033
Abstract
Description
Technical Field
[0001] This invention relates to an aqueous resin and its preparation method, and particularly to a polyacrylate emulsion with fast drying speed and its preparation method. Background Technology
[0002] Currently, the performance of water-based polyacrylate emulsion printing inks for non-permeable substrates (such as plastic films) is still difficult to match that of solvent-based inks. The main reason is that the drying speed of water-based inks cannot match that of solvent-based inks, primarily due to the slow initial drying speed of the water-based resin, which constitutes the main component of the formulation. The performance of inks depends not only on the ink coating formulation and resin structure but also on the film-forming process. The film-forming mechanisms of emulsion printing inks and solvent-based inks differ. In solvent-based inks, polymer molecules exist in the solvent in an extended chain state. During film formation, as the solvent evaporates, the molecular chains fully diffuse and entangle, eventually forming a uniform, dense film. The film-forming process of emulsion printing inks is more complex. The polymers exist in latex particles in a chain entanglement (or cross-linking) manner. These latex particles are stably dispersed in water under the protection of emulsifiers. The film-forming process includes water evaporation, latex particle aggregation, orderly arrangement, coalescence, deformation, and the diffusion and entanglement of polymer molecular chain ends after latex particle deformation. If the initial drying properties of water-based resins can be improved during the film-forming process, the drying speed problem of water-based inks may be fundamentally solved. Summary of the Invention
[0003] The purpose of this invention is to provide a polyacrylate emulsion and its synthesis method. This emulsion has a special "hard shell-gradient core" structure, which can significantly improve the initial drying (drying of the coating surface) and complete drying (drying of the inner layer of the coating) of traditional waterborne emulsion resins while ensuring film strength. It is expected to be used as a main film-forming resin in waterborne inks on non-permeable substrates, thereby improving the drying speed of waterborne inks.
[0004] The emulsion polymer of the "hard shell-gradient core" of this invention has the following structural formula:
[0005] AA 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 )-b-(MMA n3 -co-MeMBL n4 -co-nBA n5 )-b-(MMA n6 -co-MeMBL n7 -co-nBA n8 )-b-(MMA n9 -co-MeMBL n10 -co-nBAn11 )-b-(MMA n12 -co-MeMBL n13 -co-nBA n14 )-b-(MMA n15 -co-MeMBL n16 -co-nBA n17 )-b-(MMA n18 -co-MeMBL n19 -co-nBA n20 )-b-(MMA n21 -co-Me MBL n22 -co-nBA n23 )-b-(nBA n24 )-C 13 H 25 S3;
[0006] Among them, AA 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 )Formation description of hard stone, MMA n3 -co-MeMBL n4 -co-nBA n5 MMA n6 -co-MeMBL n7 -co-nBA n8 ,
[0007] MMA n9 -co-MeMBL n10 -co-nBA n11 MMA n12 -co-MeMBL n13 -co-nBA n14 MMA n15 -co-MeMBL n16 -co-nBA n17 MMA n18 -co-MeMBL n19 -co-nBA n20 MMA n21 -co-MeMBL n22 -co-nBA n23 , nba n24 The outer layer of the nucleus is dependent on the inner layer;
[0008] Wherein, n1 = 198-328, n2 = 82-198, n3 = 52, n4 = 26, n5 = 9, n6 = 44, n7 = 22, n8 = 17, n9 = 32, n10 = 16, n11 = 32, n12 = 26, n13 = 13, n14 = 39, n15 = 20, n16 = 10, n17 = 45, n18 = 10, n19 = 5, n20 = 60, n21 = 4, n21 = 2, n23 = 65, n24 = 211.
[0009] The fast-drying waterborne resin of this invention is prepared by the following method:
[0010] Step 1: Dissolve 2.965 parts by weight of macromolecular emulsifier in 180 parts by weight of purified water to form a homogeneous aqueous phase. Then, pour this aqueous phase, along with an oil phase consisting of 19.8-32.8 parts by weight of MMA and 9.184-22.176 parts by weight of MeMBL, into the reactor and stir. Raise the reactor temperature to 70-80°C, maintain stirring, and purge with nitrogen for 30-60 minutes. Add 0.03-0.05 parts by weight of initiator, and after initiating polymerization for 15-20 minutes, add 1.7 parts by weight of alkaline reagent. Continue the reaction for 10-30 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 )-C 13 H 25 S3.
[0011] Step 2: After the first step reaction is completed, the remaining 18.8 parts by weight of MMA, 10.528 parts by weight of MeMBL, and 61.184 parts by weight of nBA mixed monomers are fed in 8 separate feeds, each feed lasting 10 minutes, with a 30-minute interval between feeds. The first feed consists of 5.2 parts by weight of MMA, 2.912 parts by weight of MeMBL, and 1.152 parts by weight of nBA; the second feed consists of 4.4 parts by weight of MMA, 2.464 parts by weight of MeMBL, and 2.176 parts by weight of nBA; the third feed consists of 3.2 parts by weight of MMA, 1.792 parts by weight of MeMBL, and 4.096 parts by weight of nBA; the fourth feed consists of 2.6 parts by weight of MMA, 1.456 parts by weight of MeMBL, and 1.456 parts by weight of MeMBL. The fifth feed monomer consists of BL and 4.992 parts by weight of nBA; the sixth feed monomer consists of 1 part by weight of MMA, 0.56 parts by weight of MeMBL and 7.68 parts by weight of nBA; the seventh feed monomer consists of 0.4 parts by weight of MMA, 0.224 parts by weight of MeMBL and 8.32 parts by weight of nBA; the eighth feed monomer consists of 27.008 parts by weight of nBA monomer.
[0012] Step 3: After the second reaction is completed, raise the reaction temperature to 85-90℃ and keep it at that temperature for 60 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 ) 壳 -b-(MMA n3 -co-MeMBL n4 -co-nBA n5 ) 梯度1 -b-(MMA n6 -co-MeMBL n7 -co-nBA n8 ) 梯度2 -b-(MMA n9 -co-MeMBL n10 -co-nBA n11 ) 梯度3 -b-(MMA n12 -co-MeMBL n13 -co-nBA n14 ) 梯度4 -b-(MMA n15 -co-MeMBL n16 -co-nBA n17 ) 梯度5 -b-(MMAn18 -co-MeMBL n19 -co-nBA n20 ) 梯度6 -b-(MMA n21 -co-MeMBL n22 -co-nBA n23 ) 梯度7 -b-(nBA n24 ) 梯度8 -C 13 H 25 S3 “hard shell-gradient core” polymer.
[0013] The structures of the above-mentioned macromolecular emulsifiers are shown below:
[0014]
[0015] This invention also provides a method for preparing the above-mentioned macromolecular emulsifier, comprising at least:
[0016] (1) Mix 3.49g of precursor, 0.2g of azobisisocyanate valerate initiator, 19.44g of acrylic acid (AA) and 96g of dioxane, remove oxygen by purging with nitrogen, and react at 80°C for 2 hours.
[0017] The structural formula of the precursor is:
[0018] The preparation of this precursor is based on existing technology, including but not limited to the reference FERGUSON CJ, HUGHES RJ, NGUYEN D, PHAM BTT, GILBERT RG, SERELIS AK, SUCH CH, HAWKETT B S. Ab initioemulsion polymerization by RAFT-controlled self-assembly[J]. Macromolecules, 2005, 38(6):2191-2204. The specific reaction formula is as follows:
[0019]
[0020] (4) Add 6.72g of MeMBL, 0.2g of azobisisocyanate valerate initiator, and 45g of dioxane. After removing oxygen by purging with nitrogen, react at 80℃ for 12 hours. The specific reaction formula is as follows:
[0021]
[0022] (5) Cool to room temperature, use cyclohexane as a precipitant to precipitate the dispersant, and vacuum dry to obtain the macromolecular emulsifier.
[0023] The alkaline reagent can be any one of sodium hydroxide, potassium hydroxide, monoethanolamine, diethanolamine, and triethanolamine, with monoethanolamine being particularly preferred.
[0024] The initiator can be any one of sodium persulfate, potassium persulfate, or hydrogen persulfate, with potassium persulfate being particularly preferred.
[0025] The purified water refers to tap water purified by passing it through an LRO PVC first-stage reverse osmosis pure water device (Shanghai Sina Light Industry Machinery Equipment Co., Ltd.) until its conductivity is no greater than 50 μS / cm (25℃).
[0026] In step 1 above, when MMA = 32.8 parts by weight and MeMBL = 9.184 parts by weight, [MMA]:[MeMBL] = 4:1, n1 = 328, n2 = 82, and the theoretical glass transition temperature of the polymer obtained by this step is 123.4℃; when MMA = 27 parts by weight and MeMBL = 15.12 parts by weight, [MMA]:[MeMBL] = 2:1, n1 = 270, n2 = 135, and the theoretical glass transition temperature of the polymer obtained by this step is 136.2℃; when MMA = 19.8 parts by weight and MeMBL = 22.176 parts by weight, [MMA]:[MeMBL] = 1:1, n1 = 198, n2 = 198, and the theoretical glass transition temperature of the polymer obtained by this step is 152.8℃. Of these three monomer feed ratios, the optimal feed combination is 27 parts by weight of MMA and 15.12 parts by weight of MeMBL, with a [MMA]:[MeMBL] ratio of 2:1, n1 = 270, n2 = 135, and a theoretical molecular weight of 45085 g / mol for the "hard shell". Experiments with monomer feeds containing higher MeMBL content failed to be successfully conducted because the strong hydrophilicity of MeMBL monomers led to reaction instability. In steps 2 and 3, with n3 = 52, n4 = 26, and n5 = 9, the theoretical molecular weight of the polymer with this degree of polymerization gradient 1 is 9264 g / mol, and the glass transition temperature is 93.3℃; with n6 = 44, n7 = 22, and n8 = 17, the theoretical molecular weight of the polymer with this degree of polymerization gradient 2 is 9040 g / mol, and the glass transition temperature is 62.9℃; with n9 = 32, n10 = 16, and n11 = 32, the theoretical molecular weight of the polymer with this degree of polymerization gradient 3 is 9088 g / mol, and the glass transition temperature is 19.2℃; with n12 = 26, n13 = 13, and n14 = 39, the theoretical molecular weight of the polymer with this degree of polymerization gradient 4 is 9048 g / mol, and the glass transition temperature is... The degree of polymerization is 2℃; n15=20, n16=10, n17=45, the theoretical molecular weight of the polymer with this degree of polymerization gradient 5 is 8880 g / mol, and the glass transition temperature is -12.7℃; n18=10, n19=5, n20=60, the theoretical molecular weight of the polymer with this degree of polymerization gradient 6 is 9240 g / mol, and the glass transition temperature is -36.6℃; n21=4, n21=2, n23=65, the theoretical molecular weight of the polymer with this degree of polymerization gradient 7 is 8944 g / mol, and the glass transition temperature is -47.7℃; n24=211, the theoretical molecular weight of the polymer with this degree of polymerization gradient 8 is 27008 g / mol, and the glass transition temperature is -55℃.In summary, the theoretical total molecular weight of the polymer with a "hard shell-gradient core" particle structure prepared by this invention is 135,000 (135K). Among them, the theoretical molecular weight of the "hard shell" segment polymer is 45K, and the "gradient core" segment polymer is composed of eight gradient segment polymers. The theoretical molecular weight of the first seven gradient polymers is 9K, and the theoretical molecular weight of the last gradient polymer is 27K. From the outermost hard shell segment to the innermost PnBA segment, the glass transition temperature gradually decreases from 136.2℃ to -55℃.
[0027] In contrast, the aforementioned colloidal particle structure with a "hard shell-gradient core" has a segment molecular weight of 45K. 硬壳 -90K 梯度核 Compared to the polymers mentioned above, this invention also synthesizes a colloidal particle structure with a "hard shell-soft core" structure and a segment molecular weight of 45K. 硬壳 -90K 软核 The polymer has a "soft-shell-hard-core" colloidal particle structure, and the molecular weight of the chain segments is also 45K. 软壳 -90K 硬核 ; and has a homogeneous colloidal particle structure with a molecular weight of 135K. 均相无规 The polymer. See the comparative examples for details (Note: It has a "soft-shell-gradient core" colloidal particle structure, and the molecular weight of the chain segments is also 45K). 软壳 -90K 梯度核 The polymer exhibits properties similar to those of a "soft-shell-hard-core" colloidal particle structure, with a segment molecular weight of 45K. 软壳 -90K 硬核 The differences are minor, so no comparison will be made.
[0028] In this invention, the synthesis of macromolecular emulsifiers and polymers utilizes the mature RAFT (Reverse Radical-Based Fiber) technology, which allows for the unambiguous determination of the product structure. RAFT technology, through the reversible degradation transfer of growing free radicals, can very effectively control monomer polymerization, achieving controllable adjustment of polymer microstructure (such as the synthesis of block copolymers) and degree of polymerization. It can be applied to homopolymerization and copolymerization systems of various monomers, is applicable to almost all vinyl monomers, and operates under reaction conditions identical to traditional free radical polymerization, making it suitable for various reaction systems such as bulk polymerization, solution polymerization, emulsion polymerization, and suspension polymerization. By controlling the order of monomer addition and the proportions of each component in the synthesis formulation, polymers with different degrees of polymerization and polymeric structures can be obtained. By synthesizing latex particles with defined molecular structures, the interference of polymer molecular weight can be eliminated, further clarifying the influence of particle structure on subsequent film-forming properties, which is a major inventive aspect of this invention.
[0029] Commercially available water-based latex granules are produced using traditional emulsion polymerization technology. The latex granules are stably dispersed in water due to the adsorption of surfactants. However, these emulsifiers are easily detached under high-speed shear, making the latex particles prone to instability. Furthermore, traditional emulsion polymerization can only prepare homopolymers or random copolymers. While core-shell nanoparticles can be produced through semi-continuous processes, the core-shell structure and composition are limited by thermodynamics and reaction kinetics, making them difficult to adjust. This invention employs RAFT emulsion polymerization technology. Based on the macromolecular RAFT emulsion polymerization mechanism, during the polymerization reaction, the amphiphilic groups on the macromolecular RAFT reagent, composed of hydrophilic segments (such as polyacrylic acid segments) and hydrophobic segments (such as polystyrene segments), remain on the surface of the latex particles, while the dithioester or trithioester groups are located inside the particles. Therefore, chain growth occurs inside the particles, with the polymer chains expanding from the inside out. During the sequential addition of monomers in the preparation of block copolymers, the first monomer added forms the outer shell, while the later monomers form the core, resulting in a core-shell structure in the latex particles. The resulting product is soap-free latex granules. The latex particles have adjustable structure, particle size, composition, and molecular weight. Compared to the common RAFT emulsifiers that use traditional hydrophobic segments such as polystyrene, this invention uses poly(methyl methacrylate-co-γ-methyl-α-methylene-γ-butyrolactone), which has relatively weaker hydrophobicity than polystyrene segments but much weaker hydrophilicity than polyacrylic acid segments, as the hydrophobic segment. Experiments have shown that the introduction of this segment not only does not reduce the emulsifying performance of the emulsifier, but also exhibits good controllability (controllable degree of polymerization) for the polymerization of the three monomers MMA, MeMBL, and nBA. This is also a major innovation of this invention.
[0030] Compared with existing technologies, the beneficial effects of this invention are as follows: The aqueous emulsion provided by this invention has a special "hard shell-gradient core" structure, which can significantly improve the initial drying properties (drying of the coating surface) and complete drying properties (drying of the inner layers of the coating) of traditional aqueous emulsion resins while ensuring film-forming strength. This emulsion also has advantages such as fine particle size, good shear resistance, excellent storage stability, and strong adhesion. It is expected to be used as a main film-forming resin in aqueous inks on non-permeable substrates, thereby improving the drying speed of water-based inks. Detailed Implementation
[0031] This invention employs a sequential addition of monomers to design and prepare a multi-block copolymer with a "hard shell-gradient core" structure. This polymer has three main characteristics. First, the polymer consists of a shell of poly(methyl methacrylate-co-γ-methyl-α-methylene-γ-butyrolactone) with a high glass transition temperature (above 120°C). This shell's glass transition temperature is significantly higher than the 100°C of hard polymers obtained through traditional emulsion polymerization (such as polystyrene and polymethyl methacrylate), which is a major improvement over traditional emulsion polymerization. This provides excellent mechanical strength for the coating after the resin dries and forms a film, while also preventing the ink from forming a skin during drying, allowing for rapid moisture evaporation. Second, the flexible core layer with a low glass transition temperature provides flexibility to the coating and adjusts the particle modulus, allowing the ink layer to densify in the later stages of drying, thereby improving the coating's adhesion. Finally, unlike traditional latex particles with a "hard shell-soft core" structure that directly transition from a high glass transition temperature to a low glass transition temperature, the latex particles prepared in this invention gradually transition from a high glass transition temperature shell (above 120°C) to a low glass transition temperature inner layer (-55°C) through numerous gradient segments. This provides sufficient channels for the dehydration of the inner layer segments, unlike traditional "hard shell-soft core" latex particles, which are prone to "drying on the surface but not inside" defects due to the large difference in glass transition temperatures between the shell and core layers (this is the core inventive aspect of this invention).
[0032] In this invention, MMA is methyl methacrylate, MeMBL is γ-methyl-α-methylene-γ-butyrolactone, and nBA is n-butyl acrylate.
[0033] The present invention will be further described below with reference to the embodiments.
[0034] In the following examples, the precursor was prepared using the method described in the literature FERGUSON CJ, HUGHES RJ, NGUYEN D, PHAM B TT, GILBERT RG, SERELIS AK, SUCH CH, HAWKETT BS. Ab initio emulsion polymerization by RAFT-controlled self-assembly[J]. Macromolecules, 2005, 38(6):2191-2204. The product was determined to have the following structural formula by the test method described in the literature:
[0035] Macromolecular emulsifiers are prepared by the following methods:
[0036] (1) Mix 3.49g of precursor, 0.2g of azobisisocyanate valerate initiator, 19.44g of acrylic acid (AA) and 96g of dioxane, remove oxygen by purging with nitrogen, and react at 80°C for 2 hours.
[0037] The specific reaction formula is as follows:
[0038]
[0039] (2) Add 6.72g of MeMBL, 0.2g of azobisisocyanate valerate initiator, and 45g of dioxane. After purging with nitrogen to remove oxygen, react at 80℃ for 12 hours. The specific reaction formula is as follows:
[0040]
[0041] After cooling to room temperature, the dispersant was precipitated using cyclohexane as a precipitant, and then vacuum dried to obtain the macromolecular emulsifier.
[0042] Table 1. Characterization results of molecular weight of macromolecular emulsifiers
[0043] first step 2293 2306 1.14 Step 2 2965 2989 1.23
[0044] GPC (gel permeation chromatography) analysis showed that its molecular weight increased in segments with the addition of AA and MeMBL monomers, and the measured molecular weight was basically consistent with the designed molecular weight, indicating good controllability. Its structural formula is as follows:
[0045]
[0046] The particle size of the waterborne resin was tested using a Malvern Zetasizer 3000 HAS particle size analyzer at a temperature of 25°C.
[0047] The storage stability of waterborne resins refers to the resin's ability to remain stable for more than 12 months after standing at 60°C for 18 days without precipitation or stratification.
[0048] The shear stability of water-based resin refers to the water-based resin being dispersed at a high speed of 5000 rpm for 40 minutes on an intelligent dispersion mill (Hangzhou Qiwei Instrument Co., Ltd.), and then filtered through a 200-mesh stainless steel filter screen. The absence of filter residue on the filter screen indicates good shear stability of the water-based resin.
[0049] The glass transition temperature of the waterborne resin was determined on a PE DSC7 instrument under a nitrogen atmosphere, with the temperature increased from 40°C to 200°C at a rate of 10°C / min. Each sample was heated at 160°C for 2 min before testing to eliminate thermal history.
[0050] The monomer conversion rate was determined by gravimetric method.
[0051] The molecular weight of the polymer was characterized by gel permeation chromatography on a Waters 1525-2414-717 GPC instrument, with tetrahydrofuran as the eluent and narrow-distribution polystyrene standard as the calibration.
[0052] The adhesion test of water-based resins shall be carried out in accordance with GB / T 13217.7-2009. The resin adhesion strength is considered to be excellent if the resin adhesion strength is ≥95%.
[0053] The initial drying properties of waterborne resins shall be determined in accordance with GB / T 13217.5-2008.
[0054] The drying properties of the water-based resin are tested as follows: The water-based resin of this invention is coated onto PVC furniture film using a KPP gravure printing machine and dried at 50°C for 5 seconds. Then, an adhesion test is performed (according to GB / T 13217.7-2009). If the resin adhesion strength is ≥95%, the resin is considered to have excellent drying properties.
[0055] Example 1 ("Hard-shell-gradient core" latex particles 45K) 硬壳 -90K 梯度核 Polymer, wherein the hard-shell monomer feed composition is [MMA]:[MeMBL] = 2:1):
[0056] Step 1: Dissolve 2.965 parts by weight of macromolecular emulsifier in 180 parts by weight of purified water to form a homogeneous aqueous phase. Then, pour this aqueous phase, along with an oil phase consisting of 27 parts by weight of MMA and 15.12 parts by weight of MeMBL, into the reactor and stir. Raise the reactor temperature to 70°C, maintain stirring, and purge with nitrogen for 30 minutes. Add 0.03 parts by weight of potassium persulfate to initiate polymerization. Add 1.7 parts by weight of sodium hydroxide after 15 minutes of initiation, and continue the reaction for 10 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 )-C 13 H 25 S3 is labeled as process sample 0.
[0057] Step 2: After the first step reaction is completed, the remaining 18.8 parts by weight of MMA, 10.528 parts by weight of MeMBL and 61.184 parts by weight of nBA mixed monomers are fed in 8 batches, each batch lasting 10 minutes, with an interval of 30 minutes between each batch.
[0058] The first feed mixture consisted of 5.2 parts by weight of MMA, 2.912 parts by weight of MeMBL and 1.152 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes. The resulting product was extracted and labeled as process sample 1.
[0059] The second feed mixture consisted of 4.4 parts by weight of MMA, 2.464 parts by weight of MeMBL and 2.176 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes. The resulting product was extracted and labeled as process sample 2.
[0060] The third feed mixture consisted of 3.2 parts by weight of MMA, 1.792 parts by weight of MeMBL and 4.096 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes. The resulting product was extracted and labeled as process sample 3.
[0061] The fourth feed mixture consisted of 2.6 parts by weight of MMA, 1.456 parts by weight of MeMBL and 4.992 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes. The resulting product was extracted and labeled as process sample 4.
[0062] The fifth feed mixture consisted of 2 parts by weight of MMA, 1.12 parts by weight of MeMBL and 5.76 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes. The resulting product was extracted and labeled as process sample 5.
[0063] The sixth feed mixture consisted of 1 part by weight of MMA, 0.56 parts by weight of MeMBL and 7.68 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes. The resulting product was extracted and labeled as process sample 6.
[0064] The seventh feed mixture consisted of 0.4 parts by weight of MMA, 0.224 parts by weight of MeMBL and 8.32 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes. The resulting product was extracted and marked as process sample 7.
[0065] After the eighth feed of 27.008 parts by weight of nBA monomer was completed, the mixture was stirred and reacted for 30 minutes. The resulting product was extracted and marked as process sample 8.
[0066] Step 3: After the second reaction is completed, raise the reaction temperature to 85℃ and keep it at that temperature for 60 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 ) 壳 -b-(MMA n3 -co-MeMBL n4 -co-nBA n5 ) 梯度1 -b-(MMA n6 -co-MeMBL n7 -co-nBA n8 ) 梯度2 -b-(MMA n9-co-MeMBL n10 -co-nBA n11 ) 梯度3 -b-(MMA n12 -co-MeMBL n13 -co-nBA n14 ) 梯度4 -b-(MMA n15 -co-MeMBL n16 -co-nBA n17 ) 梯度5 -b-(MMA n18 -co-MeMBL n19 -co-nBA n20 ) 梯度6 -b-(MMA n21 -co-MeMBL n22 -co-nBA n23 ) 梯度7 -b-(nBA n24 ) 梯度8 -C 13 H 25 S3 “hard shell-gradient core” polymer.
[0067] Table 2 Polymer characterization data from Example 1
[0068]
[0069]
[0070] As shown in Table 2, with the addition of monomers at each stage, the conversion rate of monomers at each stage is close to complete; the molecular weight of the polymer gradually increases, and the measured molecular weight is basically consistent with the theoretical molecular weight. The molecular weight distribution of the polymer is narrow, all below 1.5, proving that the entire synthesis process is controllable. The total molecular weight of the polymer is 135,000 (135K), of which the molecular weight of the "hard shell" segment polymer is 45K, the "gradient core" segment polymer is composed of eight gradient segment polymers, the theoretical molecular weight of the first seven gradient polymers is about 9K, and the theoretical molecular weight of the last gradient polymer is 27K, from the outermost hard shell segment of the particle to the innermost PnBA segment. On the other hand, from the characterization of the polymer's glass transition temperature, when only the hard-shell segment is present, the polymer is a random copolymer with a glass transition temperature of 136.2℃; when only the hard-shell-gradient 1 segment is present, the polymer is a diblock polymer, exhibiting two glass transition temperatures, one for the hard-shell segment and one for the gradient 1 segment; as the number of gradient segments increases, the molecular segments other than the hard-shell segment gradually exhibit a broad transition plateau, without showing a distinct glass transition temperature; at the end of the final product synthesis, except for the hard-shell segment which still exhibits a characteristic glass transition, the remaining segments show a broad transition plateau, extending from about -55℃ to about 100℃, which also proves the formation of the gradient copolymer. These results indicate that the present invention yields the target-designed particle structure with a "hard-shell-gradient core" structure and a segment molecular weight of 45K. 硬壳 -90K 梯度核 Polymers.
[0071] Comparative Example 1 ("Hard-shell-soft-core" latex particles 45K) 硬壳 -90K 软核 Polymer (all monomer compositions are consistent with Example 1):
[0072] Step 1: Dissolve 2.965 parts by weight of macromolecular emulsifier in 180 parts by weight of purified water to form a homogeneous aqueous phase. Then, pour this aqueous phase, along with an oil phase consisting of 27 parts by weight of MMA and 15.12 parts by weight of MeMBL, into the reactor and stir. Raise the reactor temperature to 70°C, maintain stirring, and purge with nitrogen for 30 minutes. Add 0.03 parts by weight of potassium persulfate to initiate polymerization. Add 1.7 parts by weight of sodium hydroxide after 15 minutes of initiation, and continue the reaction for 10 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 )-C 13 H 25 S3 “hard shell” polymer.
[0073] Step 2: After the first step reaction is completed, add 90 parts by weight of nBA monomer into the reactor within 60 minutes to continue the reaction.
[0074] Step 3: After the second reaction is completed, raise the reaction temperature to 85℃ and keep it at that temperature for 60 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 ) 壳 -bP(nBA) 核 -C 13 H 25 S3 “hard-shell-soft-core” polymer.
[0075] Table 3 Polymer characterization data for Comparative Example 1
[0076]
[0077] Table 3 shows that with the addition of monomers at each stage, the conversion rate of monomers at each stage is close to complete; the polymer molecular weight gradually increases, and the measured molecular weight is basically consistent with the theoretical molecular weight. The polymer molecular weight distribution is narrow, all below 1.5, proving that the entire synthesis process is controllable. The total molecular weight of the polymer is 135,000 (135K), of which the molecular weight of the "hard shell" segment is 45K and the molecular weight of the "soft core" segment is 90K. The polymer has two characteristic glass transition temperatures, corresponding to the hard shell segment and the soft core segment, respectively. The above structure proves that Comparative Example 1 obtained the target-designed particle structure with a "hard shell-soft core" structure and a segment molecular weight of 45K. 硬壳 -90K 软核 Polymers.
[0078] Comparative Example 2 ("Soft-shell-hard-core" latex granules 45K) 软壳 -90K 硬核 polymer):
[0079] Step 1: Dissolve 2.965 parts by weight of macromolecular emulsifier in 180 parts by weight of purified water to form a homogeneous aqueous phase. Then add 42 parts by weight of nBA monomer and raise the reactor temperature to 70°C. While stirring, purge with nitrogen for 30 minutes, then add 0.03 parts by weight of potassium persulfate to initiate polymerization. After 15 minutes, add 1.7 parts by weight of sodium hydroxide and continue the reaction for 10 minutes to obtain AA. 28 -b-MeMBL6-bP(nBA) 壳 -C 13 H 25 S3 “soft shell” polymer.
[0080] Step 2: After the first step reaction is completed, the oil phase consisting of 57.8 parts by weight of MMA and 32.368 parts by weight of MeMBL is poured into the reactor and stirred and mixed for 60 minutes.
[0081] Step 3: After the second reaction is completed, raise the reaction temperature to 85℃ and keep it at that temperature for 60 minutes to obtain AA. 28 -b-MeMBL6-bP(nBA) 壳 b-(MMA-co-MeMBL) 核 --C 13 H 25 S3 “soft-shell-hard-core” polymer.
[0082] Table 4. Polymer characterization data for Comparative Example 2
[0083]
[0084] Table 4 shows that with the addition of monomers at each stage, the conversion rate of monomers at each stage is close to complete; the polymer molecular weight gradually increases, and the measured molecular weight is basically consistent with the theoretical molecular weight. The polymer molecular weight distribution is narrow, all below 1.5, proving that the entire synthesis process is controllable. The total molecular weight of the polymer is 135,000 (135K), of which the molecular weight of the "soft shell" segment is 45K and the molecular weight of the "hard core" segment is 90K. The polymer has two characteristic glass transition temperatures, corresponding to the soft shell segment and the hard core segment, respectively. The above structure proves that the target design with a "soft shell-hard core" particle structure was obtained by comparison with Example 2, with a segment molecular weight of 45K. 软壳 -90K 硬核 Polymers.
[0085] Comparative Example 3 (homogeneous latex particles 135K) 均相无规 Polymer (all monomer compositions are consistent with Example 1):
[0086] Step 1: Dissolve 2.965 parts by weight of macromolecular emulsifier in 180 parts by weight of purified water to form a homogeneous aqueous phase. Then add an oil phase consisting of 45.8 parts by weight of MMA, 25.648 parts by weight of MeMBL, and 61.184 parts by weight of nBA monomer. Raise the reactor temperature to 70°C, keep stirring, and purge with nitrogen for 30 minutes. Then add 0.03 parts by weight of potassium persulfate to initiate polymerization. Add 1.7 parts by weight of sodium hydroxide after 15 minutes and continue for 120 minutes.
[0087] Step 2: After the reaction in the first step is completed, raise the reaction temperature to 85℃ and keep it at that temperature for 60 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA-co-MeMBL-co-nBA)--C 13 H 25 S3 is a "homogeneous random" polymer.
[0088] Table 5. Polymer characterization data for Comparative Example 3
[0089]
[0090] Table 5 shows that the conversion rate of the reactants is close to complete; the measured molecular weight of the polymer is basically consistent with the theoretical molecular weight, and the polymer molecular weight distribution is narrow, at 1.45, proving that the entire synthesis process is controllable; the total molecular weight of the polymer is 135,000 (135K), and the polymer has a characteristic glass transition temperature. These structural results demonstrate that, compared with Example 32, the target design with a "homogeneous random" colloidal particle structure was obtained, with a segment molecular weight of 135K. 均相无规 Polymers.
[0091] Comparative Example 4 ("Hard-shell-soft-core" latex particles 45K) 硬壳 -90K 软核 Polymer (all monomer compositions are consistent with Example 1):
[0092] Step 1: Same as Example 1.
[0093] Step 2: After the first step reaction is completed, 18.8 parts by weight of MMA, 10.528 parts by weight of MeMBL and 61.184 parts by weight of nBA mixed monomers are fed in 7 batches, each batch lasting 10 minutes, with an interval of 30 minutes between each batch.
[0094] The first feed mixture consisted of 5.2 parts by weight of MMA, 2.912 parts by weight of MeMBL and 1.152 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes.
[0095] The second feed mixture consisted of 4.4 parts by weight of MMA, 2.464 parts by weight of MeMBL and 2.176 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes.
[0096] The third feed mixture consisted of 3.2 parts by weight of MMA, 1.792 parts by weight of MeMBL and 4.096 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes.
[0097] The fourth feed mixture consisted of 2.6 parts by weight of MMA, 1.456 parts by weight of MeMBL and 4.992 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 30 minutes.
[0098] The fifth feed mixture consisted of 3.4 parts by weight of MMA, 1.904 parts by weight of MeMBL and 48.4928 parts by weight of nBA. After the feed was completed, the mixture was stirred and reacted for 60 minutes.
[0099] Step 3: After the second reaction is completed, raise the reaction temperature to 85°C and keep it at that temperature for 60 minutes to obtain the product.
[0100] Table 6. Polymer characterization data for Comparative Example 4.
[0101]
[0102] As shown in Table 6, when the "8-gradient" core layer designed in Example 1 was reduced to a "5-gradient" core layer, two characteristic glass transition regions appeared in the core layer, and the gradient core structure with a wide transition plateau designed in Example 1 could not be prepared. Experiments show that the "6-gradient" and "7-gradient" core layers gradually show a wide transition plateau, and at the "8-gradient" level, as shown in Example 1, the designed gradient core structure emulsion resin was prepared. In addition, when the molecular weight is further increased to "8-gradient" or higher, the polymer molecular weight distribution is as high as 3 or higher, showing uncontrollability. Therefore, this invention did not prepare emulsion resins with more gradients, i.e., higher molecular weights.
[0103] Example 2 ("Hard-shell-gradient core" latex particles 45K) 硬壳 -90K 梯度核 Polymer, wherein the hard-shell monomer feed composition is [MMA]:[MeMBL] = 4:1):
[0104] Step 1: Dissolve 2.965 parts by weight of macromolecular emulsifier in 180 parts by weight of purified water to form a homogeneous aqueous phase. Then, pour this aqueous phase, along with the oil phase consisting of 32.8 parts by weight of MMA and 9.184 parts by weight of MeMBL, into the reactor and stir. Raise the reactor temperature to 80°C, maintain stirring, and purge with nitrogen for 60 minutes. Add 0.05 parts by weight of sodium persulfate to initiate polymerization. Add 1.7 parts by weight of monoethanolamine after 20 minutes of initiation, and continue the reaction for another 30 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 )-C 13 H 25 S3 “hard shell” polymer.
[0105] Step 2: After the first step reaction is completed, the remaining 18.8 parts by weight of MMA, 10.528 parts by weight of MeMBL, and 61.184 parts by weight of nBA mixed monomers are fed in 8 separate feeds, each feed lasting 10 minutes, with a 30-minute interval between feeds. The first feed consists of 5.2 parts by weight of MMA, 2.912 parts by weight of MeMBL, and 1.152 parts by weight of nBA; the second feed consists of 4.4 parts by weight of MMA, 2.464 parts by weight of MeMBL, and 2.176 parts by weight of nBA; the third feed consists of 3.2 parts by weight of MMA, 1.792 parts by weight of MeMBL, and 4.096 parts by weight of nBA; the fourth feed consists of 2.6 parts by weight of MMA, 1.456 parts by weight of MeMBL, and 1.456 parts by weight of MeMBL. The fifth feed monomer consists of BL and 4.992 parts by weight of nBA; the sixth feed monomer consists of 1 part by weight of MMA, 0.56 parts by weight of MeMBL and 7.68 parts by weight of nBA; the seventh feed monomer consists of 0.4 parts by weight of MMA, 0.224 parts by weight of MeMBL and 8.32 parts by weight of nBA; the eighth feed monomer consists of 27.008 parts by weight of nBA monomer.
[0106] Step 3: After the second reaction is completed, raise the reaction temperature to 90℃ and keep it at that temperature for 60 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 ) 壳 -b-(MMA n3 -co-MeMBL n4 -co-nBA n5 ) 梯度1 -b-(MMA n6 -co-MeMBL n7 -co-nBA n8 ) 梯度2 -b-(MMA n9 -co-MeMBL n10 -co-nBA n11 ) 梯度3 -b-(MMA n12 -co-MeMBL n13 -co-nBA n14 ) 梯度4 -b-(MMA n15 -co-MeMBL n16 -co-nBA n17 ) 梯度5 -b-(MMAn18 -co-MeMBL n19 -co-nBA n20 ) 梯度6 -b-(MMA n21 -co-MeMBL n22 -co-nBA n23 ) 梯度7 -b-(nBA n24 ) 梯度8 -C 13 H 25 S3 “hard shell-gradient core” polymer.
[0107] Table 7 Polymer characterization data from Example 2
[0108]
[0109] Table 6 shows that the monomer conversion rate during the reaction process was nearly complete; the polymer molecular weight gradually increased, and the measured molecular weight was basically consistent with the theoretical molecular weight. The polymer molecular weight distribution was narrow, all below 1.5, proving that the entire synthesis process was controllable. The total molecular weight of the polymer was 135,000 (135K), of which the molecular weight of the "hard shell" segment was 45K, and the "gradient core" segment consisted of eight gradient segments. The theoretical molecular weight of the first seven gradient segments was approximately 9K, and the theoretical molecular weight of the last gradient segment was 27K, from the outermost hard shell segment to the innermost PnBA segment. On the other hand, from the characterization of the polymer glass transition temperature, when only the hard shell segment was present, the polymer was a random copolymer with a glass transition temperature of 123.7℃. At the end of the final product synthesis, in addition to the characteristic glass transition of the hard shell segment, the remaining segments showed a wide transition plateau, extending from about -55℃ to about 100℃, which also proved the formation of the gradient copolymer. The above results show that the present invention obtained the target-designed particle structure with a "hard shell-gradient core" structure and a segment molecular weight of 45K. 硬壳 -90K 梯度核 Polymers.
[0110] Example 3 ("Hard-shell-gradient core" latex particles 45K) 硬壳 -90K 梯度核 Polymer, wherein the hard-shell monomer feed composition is [MMA]:[MeMBL]=1:1):
[0111] Step 1: Dissolve 2.965 parts by weight of macromolecular emulsifier in 180 parts by weight of purified water to form a homogeneous aqueous phase. Then, pour this aqueous phase, along with the oil phase consisting of 19.8 parts by weight of MMA and 22.176 parts by weight of MeMBL, into the reactor and stir. Raise the reactor temperature to 70°C, maintain stirring, and purge with nitrogen for 50 minutes. Add 0.03 parts by weight of potassium persulfate to initiate polymerization. Add 1.7 parts by weight of diethanolamine after 15 minutes of initiation, and continue the reaction for 10 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 )-C 13 H 25 S3 “hard shell” polymer.
[0112] Step 2: After the first step reaction is completed, the remaining 18.8 parts by weight of MMA, 10.528 parts by weight of MeMBL, and 61.184 parts by weight of nBA mixed monomers are fed in 8 separate feeds, each feed lasting 10 minutes, with a 30-minute interval between feeds. The first feed consists of 5.2 parts by weight of MMA, 2.912 parts by weight of MeMBL, and 1.152 parts by weight of nBA; the second feed consists of 4.4 parts by weight of MMA, 2.464 parts by weight of MeMBL, and 2.176 parts by weight of nBA; the third feed consists of 3.2 parts by weight of MMA, 1.792 parts by weight of MeMBL, and 4.096 parts by weight of nBA; the fourth feed consists of 2.6 parts by weight of MMA, 1.456 parts by weight of MeMBL, and 1.456 parts by weight of MeMBL. The fifth feed monomer consists of BL and 4.992 parts by weight of nBA; the sixth feed monomer consists of 1 part by weight of MMA, 0.56 parts by weight of MeMBL and 7.68 parts by weight of nBA; the seventh feed monomer consists of 0.4 parts by weight of MMA, 0.224 parts by weight of MeMBL and 8.32 parts by weight of nBA; the eighth feed monomer consists of 27.008 parts by weight of nBA monomer.
[0113] Step 3: After the second reaction is completed, raise the reaction temperature to 85℃ and keep it at that temperature for 60 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 ) 壳 -b-(MMA n3 -co-MeMBL n4 -co-nBA n5 ) 梯度1 -b-(MMA n6-co-MeMBL n7 -co-nBA n8 ) 梯度2 -b-(MMA n9 -co-MeMBL n10 -co-nBA n11 ) 梯度3 -b-(MMA n12 -co-MeMBL n13 -co-nBA n14 ) 梯度4 -b-(MMA n15 -co-MeMBL n16 -co-nBA n17 ) 梯度5 -b-(MMA n18 -co-MeMBL n19 -co-nBA n20 ) 梯度6 -b-(MMA n21 -co-MeMBL n22 -co-nBA n23 ) 梯度7 -b-(nBA n24 ) 梯度8 -C 13 H 25 S3 “hard shell-gradient core” polymer.
[0114] Table 8 Polymer characterization data from Example 3
[0115]
[0116] As shown in Table 7, the monomer conversion rate during the reaction process was close to complete; the polymer molecular weight gradually increased, and the measured molecular weight was basically consistent with the theoretical molecular weight. The polymer molecular weight distribution was relatively narrow, around 1.5. Compared with Examples 1 and 2, the molecular weight distribution of the hard-shell segment polymer in Example 3 was slightly wider. This is because the MeMBL monomer has strong hydrophilicity, and when its content in the mixed monomer composition is high, the reaction tends to run out of control (but within the range of [MMA]:[MeMBL]≤1:1, the overall controllability is still good). As shown in Table 7, the total molecular weight of the polymer obtained in Example 3 was 135,000 (135K), of which the molecular weight of the "hard-shell" segment polymer was 45K, and the "gradient core" segment polymer consisted of eight gradient segment polymers. The theoretical molecular weight of the first seven gradient polymers was about 9K, and the theoretical molecular weight of the last gradient polymer was 27K, from the outermost hard-shell segment to the innermost PnBA segment. On the other hand, from the characterization of the polymer's glass transition temperature, when only the hard-shell segments are present, the polymer is a random copolymer with a glass transition temperature reaching 153℃. At the end of the final product synthesis, in addition to the characteristic glass transition of the hard-shell segments, the remaining segments exhibit a broad transition plateau, extending from approximately -55℃ to approximately 100℃, which also proves the formation of a gradient copolymer. These results indicate that the present invention yields the target-designed particle structure with a "hard-shell-gradient core" structure and a segment molecular weight of 45K. 硬壳 -90K 梯度核 Polymers.
[0117] Table 9 Performance data for each embodiment
[0118]
[0119] As shown in Table 8, the waterborne resin prepared by this invention has a finer particle size, a narrower particle size distribution, good storage stability, strong shear stability, and excellent adhesion. These properties all reach the level of commercially available resins. Regarding initial drying and complete drying, the resins of Examples 1, 2, and 3 show significantly better performance than other comparative examples and commercially available resins. This is because the particles prepared by this invention gradually transition from a high glass transition temperature shell (above 120°C) to a low glass transition temperature inner layer (-55°C) through numerous gradient segments. This provides sufficient channels for the dehydration of the inner layer segments, unlike traditional "hard shell-soft core" latex particles, which are prone to "surface dry, interior not dry" drying defects due to the large difference in glass transition temperatures between the shell and core layers. Furthermore, "soft shell-hard core" and "homogeneous random" latex particles tend to have poor initial drying due to their lower surface glass transition temperatures. A comparison of Example 1 and Comparative Example 4 shows that the core layer structure requires strict control. An 8-gradient core layer feed design was used to prepare a core layer structure with a gradient structure, improving the resin's drying performance. Based on the controllability of the polymer molecular weight and the final performance of the products in Examples 1, 2, and 3, the resin of Example 1 shows better overall performance than the resins of Examples 2 and 3, proving that the optimal feed composition for the "hard shell" monomer segment is [MMA]:[MeMBL] = 2:1.
[0120] The above structure shows that the waterborne resin of the present invention can significantly improve the initial drying properties (drying of the coating surface) and the complete drying properties (drying of the inner layer of the coating) of traditional waterborne emulsion resins, and is expected to be used as the main film-forming resin in waterborne inks on non-permeable substrates, thereby improving the drying speed of waterborne inks.
[0121] The above embodiments are used to explain and illustrate the present invention, but not to limit the present invention. Any modifications and changes made to the present invention within the spirit and scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A polyacrylate emulsion, characterized in that, This emulsion has a "hard shell-gradient core" structure, as shown in the following structural formula: AA 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 )-b-(MMA n3 -co-MeMBL n4 -co-nBA n5 )-b-(MMA n6 -co-MeMBL n7 -co-nBA n8 )-b-(MMA n9 -co-MeMBL n10 -co-nBA n11 )-b-(MMA n12 -co-MeMBL n13 -co-nBA n14 )-b-(MMA n15 -co-MeMBL n16 -co-nBA n17 )-b-(MMA n18 -co-MeMBL n19 -co-nBA n20 )-b-(MMA n21 -co-MeMBL n22 -co-nBA n23 )-b-(nBA) n24 ) -C 13 H 25 S3; Among them, AA 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 ) forms the hard shell, MMA n3 -co-MeMBL n4 -co-nBA n5 MMA n6 -co-MeMBL n7 -co-nBA n8 MMA n9 -co-MeMBL n10 -co-nBA n11 MMA n12 -co-MeMBL n13 -co-nBA n14 MMA n15 -co-MeMBL n16 -co-nBA n17 MMA n18 -co-MeMBL n19 -co-nBA n20 MMA n21 -co-MeMBL n22 -co-nBA n23 nBA n24 The core layers form sequentially from the outside in; n1=198~328, n2=82~198, n3=52, n4=26, n5=9, n6=44, n7=22, n8=17, n9=32, n10=16, n11=32, n12=26, n13=13, n14=39, n15=20, n16=10, n17=45, n18=10, n19=5, n20=60, n21=4, n22=2, n23=65, n24=211; The preparation method of this emulsion includes: Step 1: Dissolve 2.965 parts by weight of macromolecular emulsifier in 180 parts by weight of purified water to form a homogeneous aqueous phase. Then, pour this aqueous phase, along with an oil phase consisting of 19.8-32.8 parts by weight of MMA and 9.184-22.176 parts by weight of MeMBL, into a reactor and stir to mix. Raise the reactor temperature to 70-80°C, maintain stirring, and purge with nitrogen for 30-60 minutes. Then, add 0.03-0.05 parts by weight of initiator and initiate polymerization for 15-20 minutes. Add 1.7 parts by weight of alkaline reagent and continue the reaction for 10-30 minutes to obtain AA. 28 -b-MeMBL6-b-(MMA n1 -co-MeMBL n2 )-C 13 H 25 S3; The structure of the macromolecular emulsifier is shown below: ; Step 2: After the first step reaction is complete, add MMA, MeMBL, and nBA in the following proportions: First feed: 5.2 parts by weight of MMA, 2.912 parts by weight of MeMBL and 1.152 parts by weight of nBA; Second feed: 4.4 parts by weight of MMA, 2.464 parts by weight of MeMBL and 2.176 parts by weight of nBA; The third feed consisted of 3.2 parts by weight of MMA, 1.792 parts by weight of MeMBL, and 4.096 parts by weight of nBA. Fourth feed: 2.6 parts by weight of MMA, 1.456 parts by weight of MeMBL and 4.992 parts by weight of nBA; Fifth feed: 2 parts by weight of MMA, 1.12 parts by weight of MeMBL and 5.76 parts by weight of nBA; Sixth feed: 1 part by weight of MMA, 0.56 parts by weight of MeMBL and 7.68 parts by weight of nBA; Seventh feed: 0.4 parts by weight of MMA, 0.224 parts by weight of MeMBL and 8.32 parts by weight of nBA; Eighth feed: 27.008 parts by weight of nBA monomer; The above eight feedings each lasted 10 minutes, with a 30-minute interval between each feeding. Step 3: After the second reaction is completed, raise the reaction temperature to 85-90℃ and keep it at that temperature for 60 minutes to obtain a polyacrylate emulsion.
2. The polyacrylate emulsion according to claim 1, characterized in that, The values are n1=270 and n2=135.
3. The polyacrylate emulsion according to claim 1, characterized in that, The alkaline reagent is any one of sodium hydroxide, potassium hydroxide, monoethanolamine, diethanolamine, and triethanolamine.
4. The polyacrylate emulsion according to claim 1, characterized in that, The initiator is either sodium persulfate or potassium persulfate.
5. The polyacrylate emulsion according to claim 1, characterized in that, Macromolecular emulsifiers are prepared by the following methods: (1) Mix 3.49 g of precursor, 0.2 g of 4,4'-azobis(4-cyanopentanoic acid) initiator, 19.44 g of acrylic acid and 96 g of dioxane, remove oxygen by purging with nitrogen, and react at 80 °C for 2 hours; The structural formula of the precursor is: ; (2) Add 6.72 g of MeMBL, 0.2 g of 4,4'-azobis(4-cyanopentanoic acid) initiator, and 45 g of dioxane. After removing oxygen by purging with nitrogen, react at 80 °C for 12 hours. (3) Cool to room temperature, use cyclohexane as a precipitant to precipitate the dispersant, and vacuum dry to obtain the macromolecular emulsifier.
Citation Information
Patent Citations
Block copolymer containing block with glass transition temperature higher than 100 DEG C and method for preparing block copolymer
CN102746478A
Toughed transparent plastic containing glass transition temperature-adjustable block and preparation method of plastic
CN103254374A